Answer:
That can be factored:
(x +6) * (x -2)
Therefore, x = -6 and x =2
Step-by-step explanation:
For this case we have the following quadratic equation:
[tex]x ^ 2 + 4x-12 = 0[/tex]
We can factor the equation, for it, we must find two numbers that when multiplied give as result -12 and when summed give as result +4. These numbers are: +6 and -2.
Then, the factorization is given by:
[tex](x + 6) (x-2) = 0[/tex]
Thus, the solutions are:
[tex]x_ {1} = - 6\\x_ {2} = 2[/tex]
Answer:
[tex]x_ {1} = - 6\\x_ {2} = 2[/tex]